Concrete matrix based on marble powder, waste glass sludge, and crumb rubber: pathways towards sustainable concrete - Akbar, Muhammad; Hussain, Zahoor; Imran, Muhammad; Bhatti, Samiullah; Anees, Muneer (Frontiers in Materials, 2024)
This research aims to develop a sustainable concrete matrix using industrial waste materials, including marble powder, waste glass sludge (WGS), and crumb rubber from tire waste. The mechanical properties of the newly designed concrete mix, such as compressive strength, split tensile strength, and flexural strength, were evaluated. The results showed improvements in compressive strength by 5%, split tensile strength by 4%, and flexural strength by 5%. Besides, a statistical two-way analysis of variance (ANOVA) with a threshold of less than 0.001 was used, and the residual error was found to be low (4.09), both in terms of lack of fit and pure error. This research proposes a new model to assess the sustainable performance of the newly developed concrete matrix. Data was collected from 21 academic professors and structural engineers, and hypotheses were tested using partial least squares structural equation modelling. The Design Expert software was deployed to check its hypothesis, and the Smart PLS software was deployed to measure data validation. The findings demonstrate that a sustainable concrete matrix positively influences sustainable performance. The proposed model offers valuable insights for decision-makers and engineering managers, highlighting the benefits of adopting sustainable materials to enhance overall sustainability performance. Incorporating marble powder, waste glass sludge, and crumb rubber was beneficial in terms of mechanical strengths and microstructure. Overall, this research contributes to the goal of reducing CO2 emissions in the cement industry and provides practical recommendations for incorporating sustainable materials in construction practices.